8 - Pursuing Excellence in a ‘World-Class African University’: The Mamdani Affair and the Politics of Global Higher Education - Isaac A. Kamola (Journal of Higher Education in Africa, 2011)
Four years after the end of apartheid, the administrators of the University of Cape Town (UCT) suspended Mahmood Mamdani, then chair of the Centre of African Studies, from his teaching obligations because they deemed his course – ‘Problematizing Africa’ – too theoretically difficult for incoming students. The ensuing showdown between Mamdani and the university administration culminated in a spirited public debate over how to best ‘trans- form’ the historically segregated university to achieve racial integration. Less commented upon, however, is the fact that this debate coincided with UCT’s efforts to brand itself as a ‘World Class African University,’ attract greater funding from foreign institutions, privatise its campus services, and adopt National Qualifications Framework (NQF) standards. In other words, UCT – like many post-apartheid universities – was busy remaking itself into a ‘global’ university. Taken in this context, Mamdani’s argument for the importance of ‘teaching Africa in an African university’ takes on a new resonance. This article re-reads the 1998 curriculum debates as also a struggle for academic autonomy within a neoliberal university. Doing so offers the op- portunity to think about the political strategies of pedagogy, while pro- viding students and faculty a compelling model for how they might resist the neo-liberalisation of higher education within their own institutions.